(untitled) (KONFERENSIYA, 2025)
The article examines how Internet language shapes the stylistic characteristics of contemporary literary discourse. It analyzes the emergence of new communicative norms within the digital environment, addressing both the constructive and problematic aspects of these developments. Particular emphasis is placed on the proliferation of slang and graphic abbreviations, as well as their increasing presence in fiction and journalistic writing